The advantage of retrieval PEG tubes in patients with buried bumper syndrome - A case report - Gülbanu ERKAN,; Mehmet ÇOBAN,; Gökçe KAAN ATAÇ,; Aysun ÇALIŞKAN,; Bülent DEĞERTEKİN, (Turkish Journal of Gastroenterology, 2019)
-